Planning of the production capacities of a furniture production company in Cuba - Estevez Torres, Ailen (2022)
This study was carried out at the Unidad Empresarial de Base (UEB) of Muebles Ludema in Las Tunas, Cuba. Its objective was to apply a planning procedure to the company's production capacities of hotel room furniture. Research was carried out using direct observation, historical-logical, hypothetical-deductive, and analysis-synthesis methods, observation techniques, documentary review, timing of operations, and sampling by instantaneous observations to collect as much information as possible. The research revealed that the factory's productive capacities are insufficient to face current demands, so the company should determine each productive activity's capacity to achieve better production results.